SETS approach-based audiovisual media for improving the students' critical thinking skills - Sri Suriawati; Mundilarto Mundilarto (Research and Social Study Institute, 2019)
Through the conduct of the study, the researchers aim at: (1) developing audiovisual media through well-qualified SETS approach so that the audiovisual media will be feasible for implementation; (2) identifying the level of the students’ critical thinking skills after the students have made use of the SETS approach-based audiovisual media; and (3) identifying the differences on the level of the critical thinking skills between the students who make use of the SETS approach-based audiovisual media and the students who do not make use of the SETS approach-based audiovisual media. This study is a Research & Development (R&D) initiative that refers to seven steps as follows: (1) gathering the necessary information; (2) designing the product; (3) developing the preliminary product; (4) performing preliminary field experiment; (5) revising the product based on the preliminary experiment results; (6) performing the main field experiment; and (7) revising the product based on the main field experiment results. After the overall process in the study has been completed, the results of the study show that: (1) the SETS approach-based audiovisual media has already met the feasibility criteria; (2) the achievement on the students’ critical thinking skills after the implementation of the SETS approach-based audiovisual media is 0.25; and (3) there have been differences on the level of the critical thinking skills between the students who make use of the SETS approach-based audiovisual media and the students who do not make use of the SETS approach-based audiovisual media.